The uses of teaching and learning approaches: some problems in nursing education. - Akinsanya CY (West African Journal of Nursing, 2001)
This study explores the teaching and learning aspects of the integration of nursing education into higher education. The implementation of project 2000 in nursing, following the report of the United Kingdom Central Council for Nursing, Midwifery and Health Visiting (UKCC) in 1986 which resulted in the integration of former schools of nursing and midwifery into institutions of higher education. The paper also reviews the background of the development, summarises the wider academic and professional issues, arising from the changes which were proposed in the report and relevant aspects of the subsequent reforms of the National Health Service (NHS). The implications for the teaching and learning approaches of student nurse education, in the light of the introduction of project2000 programme since the integration of nursing and midwifery into higher education are discussed, It further highlighted the findings from a survey of the opinions of students and teachers in one insitution of higher education which incorporated several schools of nursing and midwifery from one county subsequently amalgamated into two colleges of Nursing and midwifery before integration into a Faculty of Health and Social Work in a University.